Peran entrepreneurial self-efficacy dalam hubungan digital competence dan opportunity recognition capacity terhadap nascent entrepreneurial behavior - Pratama, Rejas; Purwaamijaya, Btari Mariska; Hermawan, Adam (Universitas Widya Mataram, 2025)
This study addresses the intention–behavior gap in university entrepreneurship by testing how digital competence (DC) and opportunity recognition capacity (ORC) shape nascent entrepreneurial behavior (NEB) through entrepreneurial self-efficacy (ESE). A causal-confirmatory quantitative design was applied to 120 student members of HIPMI PT at Universitas Pendidikan Indonesia; data were analyzed using PLS-SEM (SmartPLS 4). Results show ORC significantly increases ESE and NEB, whereas DC affects only ESE; ESE neither predicts NEB nor mediates the effects of DC and ORC. Theoretically, the findings position ESE as necessary but not sufficient for early entrepreneurial action and identify ORC as a proximal cognitive trigger that channels capability into behavior under supportive conditions. Practically, the study recommends experiential learning and structured opportunity pipelines (e.g., project-based tasks, mentoring/incubation, market validation) to convert self-efficacy into observable nascent behavior.